The effect of online reviews on customer purchase intention for luxury cosmetic products - Sardinha, Marta Isabel Toscano (2020)
The openness of online platforms generates more information on luxury brands, and consequently,it hasincreased their online presence. The purpose of this study is to investigate the effectiveness of online reviews on customers' purchase intention for Luxury Cosmetic Products by testing the effect of the observable variables Volume, Valence, Attitude, andRisk Perception of online reviews on luxury consumers. It was conductedthrough an onlinequestionnaire with 201participants. The analysis of the responsescollectedshowed that the Volume of online reviews does not influence purchase Intention of luxurycosmetic products. Also, the Customers' Attitude towards online reviews is a significant moderator that influencesPurchase Intention.